Unicorns Gallop Rampant Through China And India: Successes And Similarities (2020)
This study aims to explore the success and characteristics of the novel business model used by Chinese and Indian unicorn firms as well as attempts to develop a framework called CEHI (Collocation, Entrepreneurship Attitudes, High Tech Startups, and Innovation) for the analysis of global unicorn firms. The liter- ature on unicorn firms is immature in business, management, and accounting (BMA) literature found in Scopus and Web of Science. To bridge this gap, this paper performs a holistic review of the existing literature, exploring and analyzing all unicorns in China and India (referred to collectively as Chindia) (89 Chinese Unicorns and 16 Indian Unicorns as of 2019) to provide insights into the phenomenon and contribute towards future avenues for research into unicorns.